The Pengembangan Aplikasi Penelusuran Jurnal Ilmiah Berbasis Web Semantik: Development of a Semantic Web Based Scientific Journal Search Application - KARAME, VAIYE EFRAIM JIRE; Jacobus, Agustinus; Ruindungan, Dirko (Universitas Sam Ratulangi, 2024)
The search system is one of the technologies that is very widely used in the current technological era. With this search system, users can search and get information easily, where with the search system, users can get a variety of information on the internet, even though this search system is very widely used and can provide a lot of information for users and often this system does not display relevant data. The ADDIE model is a generic learning/training design model that serves as a guideline in building training program tools and infrastructure that are effective, dynamic and support the performance of the training itself. This ADDIE model uses 5 development stages, namely Analyze, Design, Development, Implement, and Evaluate. The results of testing the recall value (R) show that the R value obtained is still far from 1, namely 0.34. This shows that the system has not been able to find almost all the amount of relevant information according to the amount of relevant information stored in the journal ontology. The results of testing the precision (P) value show that the P value obtained is 1. The scientific journal search system aims to assist in finding information related to journal libraries. This semantic-based search system was built and uses an ontology as a representation of knowledge-based information. System testing uses 2 test keywords to determine the level of relevance of the information produced by the system and the results obtained are a recall value of 0.34 and a precision value of 1, so it can be said that the system has a fairly high level of relevance when returning the information the user wants.